Enhanced contaminant retardation by novel modified calcium bentonite backfill in slurry trench cutoff walls. (21st February 2022) - Yang, Yu-Ling; Reddy, Krishna R.; Zhang, Tao; Fan, Ri-Dong; Fu, Xian-Lei; Du, Yan-Jun
Highlights: Polyphosphate amended backfill exhibited excellent containment of metal contamination. CaCl2 concentration slightly affected hydraulic conductivity of amended backfill. Polyphoshpate amendment retarded transport of Ca 2+ through the backfill. Polyphoshpate amendment significantly increased breakthrough time of Ca 2+. Abstract: This study aimed at assessing containment properties of slurry wall backfill containing sodium hexametaphosphate (SHMP) modified calcium bentonite to contaminated groundwater. Free swell index and flexible-wall hydraulic conductivity ( k ) tests were conducted to investigate swelling and hydraulic performances of this novel backfill. The relative concentration (RC) and cumulative mass ratio (CMR) methods were adopted to assess transport parameters including hydrodynamic dispersion coefficient ( D ) and the retardation factor ( R d ) of calcium ion (Ca 2+ ) through the backfills. The results showed negligible to moderate decrease in the swell index of the modified bentonite and the modified backfill when exposed to 5 mM and 1 M calcium chloride (CaCl2 ) solution. Permeation with CaCl2 solutions increased the short-term k of the backfill by a factor of 0.9 to 1.1 as compared to the tap water permeation. The D values varied from 1.44 × 10 –10 m 2 /s to 2.89 × 10 –10 m 2 /s regardless of the CaCl2 concentration, whereas R d was vulnerable to CaCl2 concentration. The CMR method yielded a higher coefficient of determination than the RC method, but it showed no particular advantage in evaluating the transport parameters. The SHMP-modification delayed the breakthrough time of Ca 2+ by a factor of 15 to 199 in a model slurry trench wall.